Natural saponins and macrophage polarization: Mechanistic insights and therapeutic perspectives in disease management - Xiong, Beibei; Wang, Huan; Song, Yi-Xuan; Lan, Wen-Ying; Li, Jiangtao; Wang, Fang (Frontiers in Pharmacology, 2025)
Macrophage polarization plays a pivotal role in immune homeostasis and disease progression across inflammatory, neoplastic, and metabolic disorders. Saponins, which are natural compounds with steroidal/triterpenoid structures, demonstrate therapeutic potential through immunomodulatory, anti-inflammatory, and anti-tumor activities. This study aims to highlight the potential of key saponins—such as ginsenosides, astragaloside IV, dioscin, platycodin D, pulsatilla saponins, and panax notoginseng saponins—in modulating macrophage polarization and enhancing conventional therapies, particularly in oncology. We conducted structured searches in PubMed, Google Scholar, and SciFinder (2013–2024) using controlled vocabulary, including “saponins,” “macrophage polarization,” and “therapeutic effects.” Our findings demonstrate that saponins significantly modulate immune responses and improve treatment efficacy. However, clinical translation is hindered by challenges such as poor bioavailability and safety concerns, which limit systemic exposure and therapeutic utility. To overcome these barriers, innovative delivery strategies, including nanoemulsions and engineered exosomes, are essential for enhancing pharmacokinetics and therapeutic index. Future research should prioritize elucidating the molecular mechanisms underlying saponin-mediated macrophage polarization, identifying novel therapeutic targets, and optimizing drug formulations. Addressing these challenges will enable the restoration of immune balance and more effective management of diverse diseases.